Integrasi Budaya Lokal dan Pendidikan Islam: Internalisasi Nilai Moral dalam Geguritan ”Nurani Peduli” pada Siswa Madrasah Ibtidaiyah - Ali Imron; Ari Saidul Mujazin (KURAS Institute, 2022)
Moral education plays an important role in forming superior human beings. This paper aims to describe the moral values ​​contained in poetry or Geguritan